To weigh or not to weigh. Recommendations for communicating aggregated results of buildings LCA. Issue 1 (1st September 2022) - Gomes, V; Pulgrossi, L; Gomes Da Silva, M; Balouktsi, M; Lützkendorf, T; Frischknecht, R
Abstract: Interpreting contradictory results of multiple midpoint environmental indicators is challenging task. Hence, partial or full aggregation into building single scores has gained ground for the clear message they convey. This paper helps to improve understanding of the possibilities and limitations of such practice. Partial aggregated scores of five buildings were explored, limited to the environmental indicators shared by the methods examined and inventoried for the case studies. In general, the buildings' single score ranking was maintained regardless of the aggregation approach, but rank reversal is possible if e.g., ecotoxicity impact indicators are considered. Such indicators are directly influenced by the mass of metals used in a building. Furthermore, uncertainties on their results, in LCI data and in impact and damage assessment are high, and experience with them is still limited. No single best aggregation stands out per se. All of them can play their part if officially supported to ensure that coherent weights/factors are built upon solid, up-to-date data and fair intergenerational and income equity valuation procedures. In such cases, LCA practitioners are encouraged to use single scores in addition to environmental profiles or selected indicators. Overall aggregation procedures shall be transparently described, and zero pure time preference rate and equity weighting applied and explicitly declared. Sensitivity/uncertainty analysis shall be performed to assess results robustness, potential ranking reversal risks, and the effect of different discount rates. When partial aggregation is alternatively pursued, it shall be based on endpoint categories.